The effects of the statement of cash flows and earning per share (EPS) on stock prices: Empirical study on manufacturing industry in Indonesia - Gunanta, Remon; Sherlita, Erly; Lestari, Suci Fuji (2015)
The purpose of this paper is to obtain empirical evidence on the effect of the cash flow statement and Earning per Share (EPS) on stock prices.The method used in this research is descriptive and verification method, where the data has been obtained from the Indonesia Stock Exchange Office - Bandung.This study also involves a literature search. The data is statistically analysed using SPSS 18.00.The statistical analyses conducted are the classical assumption test, multiple linear regression analysis, analysis of the coefficient of determination, t-test, and F test.This study suggests that EPS has significant influence on stock price in manufacturing companies listed on the Indonesia Stock Exchange for the period from 2008 to 2012.